Reliability and Validity of Malayalam Version of 5-Item International Index of Erectile Function - Karunakaran, Aravind (Journal of clinical and diagnostic research, 2021)
Introduction: Erectile Dysfunction (ED) is a common problem affecting men and it also negatively impacts mental health. A self administered questionnaire which is validated in local language will help in better detection of ED. Aim: To assess the reliability and validity of Malayalam version of 5 item International Index of Erectile Function (IIEF-5) in the Malayali population of India. Materials and Methods: This prospective observational study was done in Government Medical College, Thiruvananthapuram, India. A total of 136 subjects were recruited into the study after taking written informed consent. Subjects were divided into two groups. Group I included 68 subjects who had complaints of ED and group II included 68 subjects who had no complaints of ED. The subjects were administered Malayalam translated IIEF-5 at baseline and after four weeks. Results: Internal consistency of the Malayalam IIEF-5 was assessed using Cronbach’s alpha and the whole scale had an excellent internal consistency of 0.90. The 5 items had an overall Intraclass Correlation Coefficient (ICC) of 0.91 showing a good test retest reliability. The Malayalam version was also highly sensitive and specific to the change in ED after four weeks. Conclusion: This study shows that the Malayalam version of IIEF-5 is a reliable and valid tool for assessment of ED, making it useful as an initial screening tool in a clinical setting. The ease of administering and favourable diagnostic properties of Malayalam IIEF-5 can help in the reducing the number of undiagnosed cases of ED.